Chemical process and design handbook - Speight, James G. (McGraw-Hill, 2002)
Control chemical processes to get the results you wantInvaluable to chemical and environmental engineers as well as process designers, Chemical Process and Design Handbook shows you how to control chemical processes to yield desired effects efficiently and economically. The book examines each of the major chemical processes, such as reactions, separations, mixing, heating, cooling, pressure change, and particle size reduction and enlargement -- in logically arranged alphabetical chapters, providing you with an understanding of the essential qualitative analysis of each. The Handbook, from expert James Speight: Emphasizes chemical conversions -- chemical reactions applied to industrial processing Provides easy-to-understand descriptions to explain reactor type and design Describes the latest process developments and possible future improvements or changes.